High Cycle Fatigue of Al and Cu Thin Films by a Novel High-Throughput Method - Burger, Sofie (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2013)
In the last two decades, the reliability of small electronic devices used in automotive or consumer electronics gained researchers attention. Thus, there is the need to understand the fatigue properties and damage mechanisms of thin films. In this thesis a novel high-throughput testing method for thin films on Si substrate is presented. The specialty of this method is to test one sample at different strain amplitudes at the same time and measure an entire lifetime curve with only one experiment.